Assessment of Awareness, Use, Attitude and the Perceived Need for Complementary and Alternative Medicine (CAM) Education, Among Undergraduate Pharmacy Students (Nigerian Journal of Pharmaceutical Research, 2023)
Background: In Nigeria, conventional medical practice is the main form of health care but Complementary and Alternative Medicine (CAM) still enjoys widespread popularity and usage among the population. Pharmacy students, as future health professionals, have a great role to play regarding the increasing CAM use.Objective: To assess CAM awareness, use, attitude and the perceived need for its education among undergraduate pharmacy students.Method: A cross-sectional study was conducted amongst pharmacy students (n= 370) of Kaduna State University (KASU). Data were collected using both online and paper-based questionnaires by total sampling. Data were analysed using SPSS Version 22 and presented as frequencies and percentages. Student t- test and one-way ANOVA were used to compare mean scores of attitudes towards CAM across socio-demographic groups.Result: Three hundred and fifty (350) students responded to the survey of which majority (n= 280, 80.0%) had used a form of CAM in the past year. The most commonly used CAM modalities were Herbal/Botanical/Dietary Supplements (n= 240, 68.6%) and Spirituality/prayers (217, 62.0%). The least known of the CAM modalities were Homeopathy (n= 133, 38.0%) and Ayurveda (n= 181, 51.7%). Three hundred and forty-six (346) students agreed that knowledge about CAM will be useful to them as future pharmacists and 347 (99.1%) agreed that CAM should be included in the undergraduate curriculum. No statistically significant differences were obtained in mean attitudes scores.Conclusion: CAM use was common and there was a general perceived need among the students for its inclusion in the undergraduate pharmacy curriculum at KASU.